2022
DOI: 10.1039/d2ra02311c
|View full text |Cite
|
Sign up to set email alerts
|

The hydroperoxyl antiradical activity of natural hydroxycinnamic acid derivatives in physiological environments: the effects of pH values on rate constants

Abstract: Quantum chemistry calculations suggest that hydroxycinnamic acid derivatives are good natural antioxidants in aqueous solutions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 73 publications
0
7
0
Order By: Relevance
“…It has been shown to provide good performance in calculating bond dissociation energies for reactions involving radicals [ 25 ]. It has very recently been implemented to calculate the reaction pathways, including transition states, of reactions of OOH and OH radicals in aqueous solution [ 26 28 ]…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown to provide good performance in calculating bond dissociation energies for reactions involving radicals [ 25 ]. It has very recently been implemented to calculate the reaction pathways, including transition states, of reactions of OOH and OH radicals in aqueous solution [ 26 28 ]…”
Section: Methodsmentioning
confidence: 99%
“…It has been shown to provide good performance in calculating bond dissociation energies for reactions involving radicals [25]. It has very recently been implemented to calculate the reaction pathways, including transition states, of reactions of OOH and OH radicals in aqueous solution [26][27][28] Within reference 6, additional calculations of the enthalpies of a number gas-phase reactions involving radicals also illustrated that M062X/6-311 + G(3df,2p) singlepoint calculations following M062X/6-311 + G(2d,2p) optimizations can very accurately reproduce the energetics of a number of reactions involving breaking of C-O and C-C bonds to form H radicals as well as radicals of carbon and oxygen atoms such as CH 3 , OCH 3 and OH radicals.…”
Section: Methodsmentioning
confidence: 99%
“…However, the study did not account for the radical scavenging activity of RA ’s dianion state and thus concluded that RA is less active ( k = 10 3 M –1 s –1 in water, pH = 7.4) than reference antioxidants Trolox or ascorbic acid. Numerous studies confirmed that the electron donation of anion states (i.e., mono, di, or tri anion) played a determining role in the radical scavenging activity of phenolic acids, and hence, the predictions of that study require further validation.…”
Section: Introductionmentioning
confidence: 97%
“…In the present study, we want to further our ongoing program of computationally evaluating the antioxidant activity of natural products ,, by examining the thermodynamics and kinetics associated with the scavenging characteristics of RA toward the HO • /HOO • radicals. Initially, a thermodynamic assessment was conducted to evaluate the primary antiradical mechanisms pertaining to all potential RA sites.…”
Section: Introductionmentioning
confidence: 99%
“…Hydroxycinnamic acid (HCA) is one of the phytochemicals that are particularly interested in employing as part of an innovative approach for the prevention and treatment of HCC. HCA is one of the most prevalent and extensively distributed classes of phenolic acids in plants (Hoa et al 2022 ). Scientists have been interested in cinnamon acid (a derivative from HCA) because of its antioxidant, antiproliferative, antiangiogenic, and antitumor properties (Sadeghi et al 2019 ).…”
Section: Introductionmentioning
confidence: 99%